Quasi-experimental study designs series: paper 13 ; realizing the full potential of quasi-experiments for health research - Rockers, Peter C.; Bärnighausen, Till (Journal of clinical epidemiology, 2017)
Although the number of quasi-experiments conducted by health researchers has increased in recent years, there clearly remains unrealized potential for using these methods for causal evaluation of health policies and programs globally. This article proposes five prescriptions for capturing the full value of quasi-experiments for health research. First, new funding opportunities targeting proposals that use quasi-experimental methods should be made available to a broad pool of health researchers. Second, administrative data from health programs, often amenable to quasi-experimental analysis, should be made more accessible to researchers. Third, training in quasi-experimental methods should be integrated into existing health science graduate programs to increase global capacity to use these methods. Fourth, clear guidelines for primary research and synthesis of evidence from quasi-experiments should be developed. Fifth, strategic investments should be made to continue to develop new innovations in quasi-experimental methodologies. Tremendous opportunities exist to expand the use of quasi-experimental methods to increase our understanding of which health programs and policies work and which do not. Health researchers should continue to expand their commitment to rigorous causal evaluation with quasi-experimental methods, and international institutions should increase their support for these efforts.
Published online 6 April 2017
Gesehen am 18.07.2018